2003
DOI: 10.1094/mpmi.2003.16.10.945
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Methyl Ester Distribution of Homogalacturonans from Near-Isogenic Wheat Lines Resistant and Susceptible to the Wheat Stem Rust Fungus

Abstract: Plants possess an efficient nonself surveillance system triggering induced disease resistance mechanisms upon molecular recognition of microbial invaders. Successful pathogens have evolved strategies to evade or counteract these mechanisms, e.g., by the generation of suppressors. Pectic fragments produced during host cell wall degradation can act as endogenous suppressors of the hypersensitive response in wheat leaves. We have isolated and characterized homogalacturonans from cell walls of two wheat cultivars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 43 publications
0
41
1
Order By: Relevance
“…The enlarged size of plants overexpressing CBP or PME3 may be attributable to this type of PME action. It has been suggested that PMEs also have a role in resistance to fungal and bacterial pathogens (McMillan et al, 1993;Boudart et al, 1998;Wietholter et al, 2003) by affecting the physicochemical properties of the cell wall to be more accessible to cell wall-digesting enzymes (Lionetti et al, 2007). Interestingly, we did not find significant effects of CBP or PME3 on plant susceptibility to M. incognita.…”
Section: Discussioncontrasting
confidence: 67%
“…The enlarged size of plants overexpressing CBP or PME3 may be attributable to this type of PME action. It has been suggested that PMEs also have a role in resistance to fungal and bacterial pathogens (McMillan et al, 1993;Boudart et al, 1998;Wietholter et al, 2003) by affecting the physicochemical properties of the cell wall to be more accessible to cell wall-digesting enzymes (Lionetti et al, 2007). Interestingly, we did not find significant effects of CBP or PME3 on plant susceptibility to M. incognita.…”
Section: Discussioncontrasting
confidence: 67%
“…The difference in pectin release by polygalacturonases was diminished after PME treatment (LeCam et al, 1994), suggesting that differences in methylester distribution rather than total degree of esterification affected pathogen success. Moreover, in wheat (Triticum aestivum) near-isogenic lines, a blockwise distribution of methylesters was detected in lines susceptible to Puccinia graminis compared with a more random distribution in resistant lines (Wiethölter et al, 2003). In addition, the elicitor activity of OGs is dependent on the degree and distribution of methylesters (Cabrera et al, 2008;Osorio et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Monosaccharide composition of seed AGPs was determined by gas liquid chromatography (GLC) using inositol as an internal standard (Wiethö lter et al 2003). A solution containing 100 mg of AGPs was lyophilized, then methanolized in 1.5 M methanolic-HCL at 80 C overnight.…”
Section: Monosaccharide Analysismentioning
confidence: 99%